Asymmetry of the rhodopsin dimer in complex with transducin. Issue 4 (9th January 2013) - Jastrzebska, Beata; Orban, Tivadar; Golczak, Marcin; Engel, Andreas; Palczewski, Krzysztof
Abstract : A large body of evidence for G‐proteincoupled receptor (GPCR) oligomerization has accumulated over the past 2 decades. The smallest of these oligomers in vivo most likely is a dimer that buries 1000‐Å 2 intramolecular surfaces and on stimulation forms a complex with heterotrimeric G protein in 2:1 stoichiometry. However, it is unclear whether each of the monomers adopts the same or a different conformation and function after activation of this dimer. With bovine rhodopsin (Rho) and its cognate bovine G‐protein transducin (Gt ) as a model system, we used the retinoid chromophores 11‐ cis ‐retinal and 9‐ cis ‐retinal to monitor each monomer of the dimeric GPCR within a stable complex with nucleotide‐free Gt . We found that only 50% of Rho* in the Rho*‐Gt complex is trapped in a Meta II conformation, while 50% evolves toward an opsin conformation and can be regenerated with 9‐ cis‐ retinal. We also found that all ‐trans‐ retinal can regenerate chromophore‐depleted Rho*e complexed with Gt and FAK*TSA peptide containing Lys 296 with the attached all‐ trans retinoid ( m/ z of 934.5[MH] + ) was identified by mass spectrometry. Thus, our study shows that each of the monomers contributes unequally to the pentameric (2:1:1:1) complex of Rho dimer and Gt heterotrimer, validating the oligomeric structure of the complex and the asymmetry of the GPCR dimer, and revealing its structural/functional signature. This study provides a clear functional distinction between monomers of family A GPCRs in their oligomeric form.—Jastrzebska, B., Orban, T., Golczak, M., Engel, A., Palczewski, K. Asymmetry of the rhodopsin dimer in complex with transducin. FASEB J. 27, 1572–1584 (2013). www.fasebj.org